2007
DOI: 10.1017/s0022029907002634
|View full text |Cite
|
Sign up to set email alerts
|

Suitability of simplified methods for monthly and twice-monthly milk recording, and new prediction factors for the alternate a.m./p.m. method in dairy ewes under a low-input production system

Abstract: Sicilo-Sarde dairy flock test-day data were analysed (1) to check predicting ability of ten milk recording procedures, based on information from a single monthly or bimonthly milking and (2) to look for the best pair of factors for predicting daily milk yield from either morning or afternoon milkings for the alternate testing method (AT). Prior to analyses, data were adjusted for variation factors with known significant effect. Number of test-day observations was 4755 from 458 lactations of 288 ewes. Losses of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
1
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 12 publications
1
5
1
1
Order By: Relevance
“…Liu et al (2000) demonstrated that AM milking records are more reliable, and that less precise estimations are carried out with data from PM milkings. Othmane and Trabelsi (2007) obtained similar results in dairy ewes. Using seven statistical models, they determined daily milk production based on one of two daily milkings.…”
Section: Introductionsupporting
confidence: 75%
“…Liu et al (2000) demonstrated that AM milking records are more reliable, and that less precise estimations are carried out with data from PM milkings. Othmane and Trabelsi (2007) obtained similar results in dairy ewes. Using seven statistical models, they determined daily milk production based on one of two daily milkings.…”
Section: Introductionsupporting
confidence: 75%
“…The alternate methods had been reported to be the most efficient simplified milk recording designs to estimate milk yield and composition (Gabiña et al, 1986;Gonzalo et al, 2003;Othmane et al, 2006;Othmane and Trabelsi, 2007;Othmane et al, 2011); but there was no available information on the impact of their adoption on genetic parameters and animal genetic evaluation allowing them to be judged as milk recoding designs for genetic improvement programs. In our study, the genetic variance component estimation showed that the adjusted alternate methods seemed more accurate; they had the lowest residual variances which were the closest to that observed with the reference method in both monthly and bimonthly milk recording designs.…”
Section: Resultsmentioning
confidence: 99%
“…The rest of recorded flocks in the Sicilo-Sarde population are on the standard A 4 plan of testing, and all ewes are milked twice daily. Daily milk production level in the entire population ranges from 0.6 to 0.8 l (Othmane and Trabelsi, 2007).…”
Section: Datamentioning
confidence: 99%
See 2 more Smart Citations